Adsorption of 1- (2--Hydroxy - 4--Nitrophenyl azo)-2- Napthol Dye onto the Cement Kiln Dust (CKD) - Nemah Sahib Mohammed Hussian (Journal of Global Pharma Technology, 2018)
The adsorption of 1-(2¯- Hydroxy-4¯-nitrophenyl azo) -2-naphthol dye onto the Cement Kiln Dust (CKD) was studied in the temperature range 298-328K. The sorption process was examined in terms of its equilibria and kinetics. Batch adsorption experiments were conducted to evaluate the percentage removal of 1-(2--Hydroxy -4- - nitrophenyl azo)-2-napthol onto CKD waste at operation conditions of sorbate concentration, pH, contact time, sorbent dose. Time-dependent experiments for the removal efficiency required a shortest contact time, i.e , binding to the CKD was rapid and occurred within 25 min. Adsorption isotherms equations were tested for all of Langmuir, Freundlich, Temkin,3 Dobinin-Radushvich, and Elovich. The equilibrium adsorption data were fitted to Freundlich and Temkin isotherms at 298K. Adsorption followed Intra – partical - diffusion rate kinetics.   Thermodynamic parameters ΔG*, ΔH*, ΔS* and Ea were computed, and showed that the adsorption process onto CKD was exothermic and non-spontaneous. Also adsorption studies suggest that physisorption might be the major mode of adsorption and CKD expressed as low affinity for removal of 1-(2¯- Hydroxy-4¯-nitrophenyl azo) -2-naphthol Dye onto the Cement Kiln Dust  that the high percentage removal was found ≈50%  at 298K , pH=6.Keywords: Cement Kiln Dust; Azo dyes; Adsorption isotherms; Kinetic study; Thermodynamic study.